KARAKTERISTIK KEPEMIMPINAN PENDIDIKAN ISLAM BERBASIS MASJID - Ginanjar, M. Hidayat; ., Wartono (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2018)
Leadership is the ideal of quality, both in terms of physical, mental, and intellectual. Maturity in terms ofthis aspect will help a leader in carrying out the task. Knowledge and a wide perspective is the key in solving many problems that block or make some breakthroughs for the success of the important task of a leader. Islam encourage every Muslim to have these three types of power. The strong and good believers are well loved by Allah more than the weak believers, each has a virtue. For that, the vision and values of leadership comes from the ideal practices of Rasulullah peace be upon him (Shalallahu ’alaihi wa sallam) and the Companions, it is necessary and must continue to be extracted, distributed and socialized to become a strong issue in the stage of leadership in society. Therefore, a good leadership is absolutely needed by the community, and of course the leaders are expected to appear is a leader that has a nature or character laudable. That is, on the side of truth, justice, has the nature of trust, a worthy model, simplicity, greatness of the soul, forgive person, and others who emphasize kindness for the people.One of the leadership Islamic education models is leadership based mosque, the mosque is a place where Muslims join together in routines worship, both (hablum minallah) (relationship between human and Allah) or (hablum minannas) (relationship between human and human). For Muslims, the mosque become the heart moorings, the port development and the life energy of Muslims. mosques also function as institutions of education and knowledge of Islam. In addition, the mosque is also a place that can be delivered candidates Islamic leaders in the future, as evidenced (applied) by Rasulullah peace be upon him (Shalallahu ’alaihi wa sallam), he built with the friends so that future generations be able to lead the best and people through developments that centred in mosque. People were educated in mosques in a shelter of the high Islamic society and give priority in deliberation for solving problems. The mosque which was established on the basis of devotion to Allah will inure to the influence of education in human life. Thus, the mosque-based leadership can bear a good leader, the leader of a people-oriented development, so that it can be delivered to devotee individuals, able to lead and bring the next generation achieve their hopes; establishing a believer for himself, family, community, nation and state. Keyword: Islamic Education, Leadership, Caracter, Mosqul Based.